Analisis Kepuasan Customer Terhadap Produk Cokelat Almond Pada Kewirausahaan - Alfi Falah Aghnia; Rizka Inayatul Ummah; Tegar Pratama; Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Chocolate is a product made from ingredients that are very easy to find. Therefore, providing large amounts of chocolate bars can be very helpful. This way, you don't have to worry about running out of the main ingredient, which will become the most important ingredient for chocolate. Add to layer with chocolate mixture. There are still many variations and different toppings, such as almonds, walnuts, cashews, etc. Indonesia's cocoa farming industry is currently developing. Many countries in Indonesia produce nuts, especially almonds, as the primary raw material. On this occasion, the researcher hopes to create an entrepreneurial spirit with a product called "chocolate almond", which produces various types of chocolate products both on industrial and small business scales. One of the producers of processed chocolate products is Kampung Chocolate. This study aims to determine consumer satisfaction with processed almond chocolate products. In addition, this study uses descriptive analysis techniques with business feasibility studies and direct observations of products thrown by entrepreneurs to determine the characteristics of processed almond chocolate products that need improvement. It is intended that the attributes included in the level of customer satisfaction are maintained. This means that consumers are happy with processed almond chocolate products. Manufacturers must improve properties whose performance has yet to reach consumer satisfaction to increase consumer satisfaction and present a positive image for students towards ongoing business activities.